2008
DOI: 10.1186/1743-7075-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Drug/diet synergy for managing malignant astrocytoma in mice: 2-deoxy-D-glucose and the restricted ketogenic diet

Abstract: Background: Astrocytomas are largely dependent on glycolysis to satisfy their bioenergetic requirements for growth and survival. Therapies that target glycolysis can potentially manage astrocytoma growth and progression. Dietary restriction of the high fat/low carbohydrate ketogenic diet (KD-R) reduces glycolysis and is effective in managing experimental mouse and human astrocytomas. The non-metabolizable glucose analogue, 2-deoxy-D-glucose (2-DG), is a potent glycolytic inhibitor that can mimic effects of ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…It has been shown that a RKD given in combination with the glycolysis inhibitor, 2-deoxy-D-glucose, reduced the growth of a mouse CT-2A astrocytoma to a greater extent than either therapy administered alone ( 74 ). Metformin, a therapy for diabetes mellitus, and the analog phenformin are becoming a focus in the cancer metabolism research community due to their anti-tumor activity in a variety of in vitro and in vivo cancer models, including brain tumors ( 75 ); however, they have not been investigated in combination with CR or the KD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a RKD given in combination with the glycolysis inhibitor, 2-deoxy-D-glucose, reduced the growth of a mouse CT-2A astrocytoma to a greater extent than either therapy administered alone ( 74 ). Metformin, a therapy for diabetes mellitus, and the analog phenformin are becoming a focus in the cancer metabolism research community due to their anti-tumor activity in a variety of in vitro and in vivo cancer models, including brain tumors ( 75 ); however, they have not been investigated in combination with CR or the KD.…”
Section: Discussionmentioning
confidence: 99%
“…The KD-R would act as a sustained 'Press', whereas HBO 2 T and metabolic drugs would act as a 'Pulse' for the mass elimination of tumor cells in the body. Some of the cancer metabolic drugs could include 2-deoxyglucose, 3-bromopyruvate and dichloroacetate (56,120,(225)(226)(227). This therapeutic strategy produces a shift in metabolic physiology that will not only kill tumor cells but also enhance the general health and metabolic efficiency of normal cells, and consequently the whole body (189,209).…”
Section: Implications For Novel Therapeuticsmentioning
confidence: 99%
“…Previous studies with refractory pediatric astrocytoma and adult GBM suggest that ketogenic diets are therapeutically effective against malignant brain cancer (Nebeling et al, 1995;Zuccoli et al, 2010). The RKD could be even more therapeutic if combined with drugs that target glycolysis, e.g., 2-deoxyglucose or dichloroacetate (Marsh et al, 2008b;Michelakis et al, 2010). It is also possible that therapeutic synergy might occur if the type-2 diabetes drug, metformin, is administered together with the RKD (Omar et al, 2010;Oleksyszyn, 2011).…”
Section: Restricted Ketogenic Diet (Rkd) As An Alternative To the Stamentioning
confidence: 99%
“…We think that metabolic diet therapy could be enhanced when combined with drugs that also target energy metabolism. Support for this hypothesis comes from our recent pilot study showing that the non-metabolizable glycolysis inhibitor, 2-deoxy-D-glucose (2-DG), worked synergistically with the RKD to reduce CT-2A astrocytoma growth (Marsh et al, 2008b). 2-DG is readily transported into cells, is phosphorylated by hexokinase, but cannot be metabolized further and thus accumulates in the cell (Aft et al, 2002).…”
Section: Synergistic Interaction Of Rkd and 2-deoxyglucose (2-dg)mentioning
confidence: 99%
See 1 more Smart Citation